Electrospun Carbon Nanofibers as Alternative Electrode Materials for Vanadium Redox Flow Batteries. Issue 12 (17th August 2015) - Fetyan, Abdulmonem; Derr, Igor; Kayarkatte, Manoj Krishna; Langner, Joachim; Bernsmeier, Denis; Kraehnert, Ralph; Roth, Christina
Abstract: Non‐woven carbon nanofiber networks were produced by electrospinning. Electrospinning is a process that can easily be up‐scaled, producing carbon fibers that can be used as electrodes with increased surface area and reaction sites. The structure of electrospun carbon nanofibers (ES‐CNFs) was investigated by scanning electron microscopy and compared to a commercial carbon felt (CF). The electrochemical properties of the obtained ES‐CNFs were studied for the negative half‐cell reaction in a three‐electrode setup and a single‐cell battery test system. The performance and stability of the generated materials were tested by charging and discharging the cell and carrying out X‐ray diffraction and Raman spectroscopy before and after operation. An increase in the energy efficiency of about 10 % was achieved when using five sheets of free‐standing ES‐CNFs compared to commercial CFs, revealing the potential use of ES‐CNFs as electrode materials in the negative half‐cell of all‐vanadium redox flow batteries. Abstract : Conducting experiments : Carbon‐based nanofibers are produced through electrospinning, forming a free‐standing conductive network that can be used directly as an electrode in vanadium redox flow batteries. X‐ray diffraction and Raman spectroscopy are used to investigate the structure and stability of the electrospun carbon nanofibers before and after charging and discharging.